Experimental Investigation of Electromechanical Machiing and Optimization of Process Parameters Using Aluminium Alloy 7075 Electrode - K Udayani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electrochemical Machining Is Often Used For Shaping Intricate Or Non-Metallic Forms But Complex To Machine Processes. EC Is Commonly Relevant In The Aeronautics, The Security Business. It Is A Common Commodity For Aerospace Owing To The Excellent Combination Of Properties And Low Density In The Aluminum Alloys. The Ultimate Goal Of The Experimentation Is To Discover The Highest MRR And The Optimal Surface End. In This Investigation, Parametric Analysis Of ECM Was Performed To Congregate The Criteria Of Proficient Micromachining. Most Relevant Process Parameters In ECM Are Machining Voltage, Electrolyte Concentration, And Time-Pulse. Micro Machining Was Observed Under Material Removal Rate (MR) And Machining Conditions Where The Cut Diameter Was Decreased. The Final Results Of This Study Showed That Processing Voltage And Electrolyte Concentrations Are Very Significant. The Optimal Parameter Obtain Is Voltage 15V, Feed Rate 0.9 Mm/Min, Electrolyte Concentration 20 Percent. Aluminium Alloy 70 Underwent The Electrochemical Machining Validation Inspection.